Desenvolvimento de um aplicativo com estratégias da gamificação no tratamento nutricional de pacientes de cirurgia bariátrica - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
BACKGROUND: It is a fact that obesity is a global public health problem; thus, as an alternative to alleviate this problem, bariatric surgery has proven to be an effective method, which, accompanied by a Multiprofessional Team, can increase the survival of patients with this morbidity. Adherence to nutritional therapy is important since the preoperative period, to promote the success of the treatment, guaranteeing the possibility of positive responses of the organism in the face of the planned surgical intervention; however, the lack of commitment of patients, in following the nutritional protocols in this process, has a negative influence on the efficiency of the treatment. In an attempt to increase patients' adherence to diet therapy, research and development of digital technological innovations, materialized in applications for mobile devices, together with gamification aspects, used to motivate them in healthy food choices. OBJECTIVE: General: To develop an application for mobile devices with gamification strategies for patients in the treatment and monitoring of nutritional evolution in the preoperative period of bariatric surgery and to validate its usability. Specifics: Meet the Persona who will use the serious game; build an application for bariatric surgery patients; validate the application's functionalities with bariatric surgery patients. METHOD: Study of the development of an application for Android system with strategies of gamification and validation by the System Usability Scale. The following steps were followed: 1) Characterization of the Persona; 2) Planning; 3) Operating procedure, 4) Testing and Publication 5) App validation by participants RESULTS: 28 participants, female (96.4%), mean age 44.8 (7.3) years, with mean Mass Index Body weight of 45.0±3.0 kg/m2. Patients considered health as the main benefit to follow the diet (50%), but feel reluctant to stop consuming foods cited as tasty (71.4%). The Plate app choose your food, it was produced with four games and validated with Score (92.9%). CONCLUSION: The application was as rated for maximum usability. It is can be used by patients, professionals or people interested in healthy eating. It is available on the Google Play platform and to be installed free of charge.
Keywords: Cirurgia Bariátrica; Aplicativos móveis; CIENCIAS DA SAUDE: MEDICINA: CIRURGIA; Cirurgia Bariátrica; Aplicativo em dispositivos móveis; Terapia nutricional; Tecnologia